High-resolution outgoing longwave radiation dataset from Kalpana-1 satellite during 2004-2012 - Mahakur, M.; Prabhu, A.; Sharma, A. K.; Rao, V. R.; Senroy, S.; Singh, Randhir; Goswami, B. N. (Current Science, 2013)
Long record of high-resolution quality-controlled outgoing longwave radiation (OLR) from geostationary platforms like Kalpana-1 has the potential not only to provide detailed information of cloud types contributing to the measure of rain, but also helps unravel convective cloud organization in the tropics from small scale to meso- and synoptic scales. A research quality product of three hourly OLR for the period May 2004 June 2012 is produced from Kalpana-1 very high resolution radiometer (VHRR) radiances over the Indian region (40 degrees S-40 degrees N, 25-125 degrees E) in a regular grid of 0.25 x 0.25 degrees. The quality and usefulness of the dataset is demonstrated here using some illustrative examples. Although these data are available for a relatively short-period, it is shown that they will be potentially more useful than the widely used OLR from NOAA satellites in representing the annual cycles, particularly over the desert and humid oceans, due to their frequent sampling and quality. The active-break periods in the Indian summer monsoon picked up by both the OLR match well. This three hourly OLR estimated from Kalpana-1 VHRR is able to describe the fine-scale structure of the diurnal variation over the region.
Keywords: Active break periods; diurnal variation; geostationary platforms; outgoing longwave radiation